2022
DOI: 10.3390/su14052838
|View full text |Cite
|
Sign up to set email alerts
|

Application of Machine Learning Models for Predictions on Cross-Border Merger and Acquisition Decisions with ESG Characteristics from an Ecosystem and Sustainable Development Perspective

Abstract: From an ecosystem perspective, mergers and acquisitions (M&A) are one of the key paths for firms to foster complementary sectors and gain complementary assets. From the perspective of sustainable development, M&A can reallocate resources from target to asset to achieve better synergy and prolong the operation of a merged firm. However, M&A activities are characterized by high risk due to the high cost and uncertainty. Thus, a prediction model of M&A decisions is valuable for firms’ strategy des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 108 publications
(160 reference statements)
0
4
0
Order By: Relevance
“…Hong et al [37] Resource reallocation and synergy potential: complementarity for both parties can exert more potential synergy, thereby increasing the capacity of the merged firms to develop sustainably Guo et al [38] Motivation of access to natural resources. Global oil and gas M&A are mostly domestic M&A, because cross-border M&A risks are closely related to many complex political and economic relationships Zhou, Lingling et al [39] Green M&A improves operational efficiency…”
Section: Markovska Et Al [35]mentioning
confidence: 99%
See 2 more Smart Citations
“…Hong et al [37] Resource reallocation and synergy potential: complementarity for both parties can exert more potential synergy, thereby increasing the capacity of the merged firms to develop sustainably Guo et al [38] Motivation of access to natural resources. Global oil and gas M&A are mostly domestic M&A, because cross-border M&A risks are closely related to many complex political and economic relationships Zhou, Lingling et al [39] Green M&A improves operational efficiency…”
Section: Markovska Et Al [35]mentioning
confidence: 99%
“…Furthermore, pursuit of integration, solidarity, and cooperation between EU countries by consolidating energy policies has the capacity to improve EU-wide energy security. Moving from the industry to the firm level, Hong et al [37] acknowledge the synergy that pursuit of M&A may reallocate resources from target to asset and prolong the operation of the combined firms. Similarly, Zhou, Lingling, et al [39] found that green M&A improves operational efficiency and strengthens firms' development capacity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…State-owned enterprises and private enterprises have different sensitivities to industrial policy. Due to the differences in the social responsibilities of SOEs and private firms, there are also significant differences in the selection of industrial policy support targets in M&As [85]. SOEs bear more policy burdens than non-SOEs.…”
Section: The Moderating Role Of State-owned Enterprisesmentioning
confidence: 99%
“…Under the impact of the downward pressure on the economy and the impact of "black swan" events such as the new crown epidemic, enterprises are not interested in broadening financing channels, and reducing the demand for financing costs is even stronger. With the implementation of the dual carbon goals and the launch of the national carbon emission trading market, the public's attention to environmental protection and social responsibility has been unprecedentedly high [8], which has also continuously promoted the construction and development of China's ESG information disclosure [9].…”
mentioning
confidence: 99%